Tourism Climatology: Past, Present, and Future - María Belén Gómez-Martín (Atmosphere, 2021)
This special issue, entitled Tourism Climatology: Past, Present, and Future, contains seven original articles and two review reports which tackle some of the main lines of research in the field of Tourism Climatology [...]